2021
DOI: 10.1021/acs.jmedchem.1c00158
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Stable Cyclic Peptide Analgesic Derived from Sunflower Seeds that Targets the κ-Opioid Receptor for the Treatment of Chronic Abdominal Pain

Abstract: The rising opioid crisis has become a worldwide societal and public health burden, resulting from the abuse of prescription opioids. Targeting the κ-opioid receptor (KOR) in the periphery has emerged as a powerful approach to develop novel pain medications without central side effects. Inspired by the traditional use of sunflower ( Helianthus annuus ) preparations for analgesic purposes, we developed novel stabilized KOR ligands (termed as helianorphins) by incorporating different dynorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…On the other hand, all three blenny fish-derived peptides demonstrated high potency and efficacy in the cAMP assay. Previous studies identified the arginine residues at the position 6 and 7 of human dyn A 1-13 to be crucial for its high a Binding and cAMP data for dynorphin (dyn) A 1-13 have been taken from previously published literature (Muratspahić et al, 2021). b Data are from three independent experiments.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, all three blenny fish-derived peptides demonstrated high potency and efficacy in the cAMP assay. Previous studies identified the arginine residues at the position 6 and 7 of human dyn A 1-13 to be crucial for its high a Binding and cAMP data for dynorphin (dyn) A 1-13 have been taken from previously published literature (Muratspahić et al, 2021). b Data are from three independent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…All blenniorphins comprise these residues in their sequences. Hence, it is thus not surprising that they stimulate a mammalian KOR with a potency comparable to human dyn A 1-13 (Muratspahić et al, 2021). However, the rank order potency for the blenniorphans in binding vs. functional assays does not match.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations